Determination of Downy mildew and Powdery Mildew Resistance of Some Grape Cultivars and Genotypes - Atak, A. (South African Journal of Enology and Viticulture, 2017)
Different grape cultivars of Vitis species have been cultivated in Turkey since ancient times. A large proportion of these cultivars cannot be cultivated in the humid regions of the country due to downy mildew (Plasmopara viticola) and powdery mildew (Uncinula necator or syn. Erysiphe necator) diseases. Cultivars resistant to these diseases can generally grow without any or fewer fungicide applications. However, there are also differences in the resistance level of cultivars. In particular, Vitis vinifera cultivars, the most widely cultured species, are most affected by these diseases. Thirteen V. vinifera cultivars, eight V. labrusca cultivars and six interspecific cultivars were used in this study, for a total of 27 cultivars. The resistance of cultivars against downy mildew and powdery mildew was determined over two years with natural infection and artificial inoculation applications. Generally, all cultivars showed more resistance to downy mildew, while they also showed lower resistance to powdery mildew. The evaluation based on species found V. vinifera to be the most sensitive. While interspecific cultivars were found to be most resistant to downy mildew, V. labrusca cultivars were the most resistant to powdery mildew. Among cultivars of the same species, however, differences in terms of resistance were observed. These differences can be used in breeding studies in order to obtain new, disease-resistant cultivars, which may be grown commercially to comply with good agricultural practices (GAP) or organic viticulture in the future.